A comparison of visual working memory and episodic memory performance in younger and older adults. Issue 3 (4th May 2019) - Lugtmeijer, Selma; de Haan, Edward H. F.; Kessels, Roy P. C.
ABSTRACT: Working memory and episodic memory decline with age. However, as they are typically studied separately, it is largely unknown whether age-associated differences are similar. A task design was developed in which visual working memory and episodic memory performances were measured using the same stimuli, with both tasks involving context binding. A 2-back working memory task was followed by a surprise subsequent recognition memory task that assessed incidental encoding of object locations of the 2-back task. The study compared performance of younger (N=30; Mage =23.5, SDage =2.9, range=20-29) and older adults (N=29; Mage =72.1, SDage =6.8, range=62-90). Older adults performed worse than younger adults, without an interaction effect. In younger, but not in older adults, performance on the two tasks was related. We conclude that although age differences (Young>Older) are similar in the working memory and incidental associative memory tasks, the relationship between the two memory systems differs as a function of age group.